2001
DOI: 10.4049/jimmunol.167.10.6031
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Organ-Specific Autoantigen for Fas Ligand-Mediated Activation-Induced Cell Death in Murine Sjögren’s Syndrome

Abstract: Activation-induced cell death (AICD) is a well-known mechanism of peripheral T cell tolerance that depends upon an interaction between Fas and Fas ligand (FasL). In this study, we demonstrate that the administration of a soluble form of anti-FasL Ab, FLIM58, results in severe destructive autoimmune exocrinopathy in the murine model of human Sjögren’s syndrome (SS), and we found that an organ-specific autoantigen may play an important role on down-modulation of AICD. A high titer of serum autoantibodies agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…FasL can be upregulated when cells are responsive to UV irradiation or treated by cytotoxic drugs. Over expression of FasL can inhibit some autoimmue diseases by deleting auto-immune memory cells [4,5] . Moreover, Fas-FasL interaction can protect allografts from immune attack and induce anti-tumor responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FasL can be upregulated when cells are responsive to UV irradiation or treated by cytotoxic drugs. Over expression of FasL can inhibit some autoimmue diseases by deleting auto-immune memory cells [4,5] . Moreover, Fas-FasL interaction can protect allografts from immune attack and induce anti-tumor responses.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, membrane-bound FasL, or FasL is fully competent in transducing Fas-mediated signals for apoptosis and NF-kappaB nuclear translocation because membrane FasL could possess both Fas-focusing and signal transducing functions. While sFasL is known to be deficient in transducing signals upon engagement with membrane Fas [4,14] . But in some cases, sFasL was found to be involved in the deletion of potentially hazardous peripheral memory cells [10] .…”
Section: Discussionmentioning
confidence: 99%
“…34 The molecular mechanism may be mediated by activationinduced cell death (AICD), which is well known to act as a system to maintain the peripheral T cells through Fas-mediated apoptosis. [35][36][37] Activated or autoreactive T cells are considered to delete by …”
mentioning
confidence: 99%
“…B Immunohistochemical staining of CD3 + T cells was performed using the paraffin-embed sections of salivary glands from SS patients. one of salivary gland-specific autoantigens for SS and the antigen-specific response of T H 1 cells, and define the breakdown of peripheral tolerance by dysfunction of activationinduced cell death (AICD) that is a system to delete autoreactive T cells in the periphery [18,19]. Besides, several KO mice have been reported that SS-like lesions are observed in salivary or lacrimal glands.…”
Section: Figurementioning
confidence: 99%